Meningkatkan Efikasi Diri Dan Hasil Belajar Peserta Didik Melalui Model Problem Based Learning Pada Pelajaran Pendidikan Agama Katolik Dan Budi Pekerti Fase B Kelas IV di SDN 091374 Nagasaribu - Natalia Br Barus (PROSIDING SEMINAR NASIONAL PENDIDIKAN DAN AGAMA, 2024)
Education is a need that must be met by every individual and is an inseparable part of all human activities. In all conditions, humans cannot avoid the impact of the application of education in everyday life. The subjects of the study were fourth grade students in an elementary school. This study aims to improve students' self-efficacy and learning outcomes in Catholic Religious Education and Character Education through the application of the Problem Based Learning (PBL) Learning Model. The method used is Classroom Action Research (CAR) which is carried out in two cycles, focusing on students' cognitive and affective development. The results of the study showed a significant increase in students' self-efficacy, with an average increase of 10.81%, as well as an increase in involvement and positive attitudes in the learning process. And the increase in learning outcomes was 15.91%.